1984
DOI: 10.1111/j.1600-0773.1984.tb01970.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Guanine N7‐Alkylation in Mice in Vivo by the Organophosphorus Insecticides Trichlorphon, Dimethoate, Phosmet and Bromophos

Abstract: Following intraperitoneal administration to male mice (strain AB Jena/Halle) of 14C-methyl-labelled trichlorphon, dimethoate, phosmet and bromophos, 10-20 Ci/mol, in dosages of 0.06-0.55 mmol/kg, DNA from liver and kidneys was analyzed for 14C in N-7 methylguanine (7-MeG). The extents of methylation were in the range of 5-10 mumol 7-MeG/mol guanine for trichlorphon and dimethoate and of 0.2-0.4 for phosmet and bromophos, for high doses, respectively Excretion half-lives of 7-MeG were differing between trichlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Several studies have reported the genotoxic potential of OP pesticides (Bolognesi 2003), but the results reported so far are not conclusive. The main toxic effect of OP pesticides is the inhibition of acetylcholinesterase, but other mechanisms are responsible for their genotoxicity, such as those related to their alkylating (Dedek et al 1984;Mehl et al 2000) and phosphorylating properties (Piña-Guzmán et al 2005). In addition, it has been reported that OP compounds induce oxidative stress in humans (Banerjee et al 1999;Ranjbar et al 2002) and animals (Debnath and Mandal 2000;Sharma et al 2005a, b), and different types of DNA lesions have been demonstrated to arise as a result of oxidative attack including single-and double -DNA strand breaks, crosslinks, chromosomal aberrations, and DNA base oxidation (Emerit 1994;Hughes et al 1996;Lopes et al 1998;Nackerdien et al 1991;Twigg et al 1998).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have reported the genotoxic potential of OP pesticides (Bolognesi 2003), but the results reported so far are not conclusive. The main toxic effect of OP pesticides is the inhibition of acetylcholinesterase, but other mechanisms are responsible for their genotoxicity, such as those related to their alkylating (Dedek et al 1984;Mehl et al 2000) and phosphorylating properties (Piña-Guzmán et al 2005). In addition, it has been reported that OP compounds induce oxidative stress in humans (Banerjee et al 1999;Ranjbar et al 2002) and animals (Debnath and Mandal 2000;Sharma et al 2005a, b), and different types of DNA lesions have been demonstrated to arise as a result of oxidative attack including single-and double -DNA strand breaks, crosslinks, chromosomal aberrations, and DNA base oxidation (Emerit 1994;Hughes et al 1996;Lopes et al 1998;Nackerdien et al 1991;Twigg et al 1998).…”
Section: Introductionmentioning
confidence: 97%
“…Additional mechanisms, such as those related to the alkylating (Dedek et al, 1984;Mehl et al, 2000) and phosphorylating (Piña-Guzmán et al, 2005) properties of OP compounds, have also been involved in their genotoxicity and damage to sperm.…”
Section: Introductionmentioning
confidence: 99%
“…Further experimental studies could provide interesting results using in vivo techniques similar to those used in this work, which had the aim of determining whether Phosmet, as suggested by other authors, has a role in increasing the risk of developing TSEs. Some of Phosmet’s biochemical features include having a partition coefficient much higher than other organophosphate compounds (Dedek et al., 1984) and being partially composed of phthalimide. This could be correlated with a more direct effect on the illness, taking into account that the partition coefficient seems to correlate with bioaccumulation abilities as well as the degree of chronic toxicity exerted by the organophosphate compounds (Freed et al., 1979); phthalimide has been shown to disturb tyrosine kinase activities and tyrosine specific phosphorylation of certain membrane proteins (Wahby et al., 1990).…”
Section: Discussionmentioning
confidence: 99%